Altered medial prefrontal cortex and dorsal raphé activity predict genotype and correlate with abnormal learning behavior in a mouse model of autism‐associated 2p16.3 deletion. Issue 4 (10th February 2022) - Hughes, Rebecca B.; Whittingham‐Dowd, Jayde; Clapcote, Steven J.; Broughton, Susan J.; Dawson, Neil
Abstract: 2p16.3 deletion, involving NEUREXIN1 ( NRXN1 ) heterozygous deletion, substantially increases the risk of developing autism and other neurodevelopmental disorders. We have a poor understanding of how NRXN1 heterozygosity impacts on brain function and cognition to increase the risk of developing the disorder. Here we characterize the impact of Nrxn1α heterozygosity on cerebral metabolism, in mice, using 14 C‐2‐deoxyglucose imaging. We also assess performance in an olfactory‐based discrimination and reversal learning (OB‐DaRL) task and locomotor activity. We use decision tree classifiers to test the predictive relationship between cerebral metabolism and Nrxn1α genotype. Our data show that Nrxn1α heterozygosity induces prefrontal cortex (medial prelimbic cortex, mPrL) hypometabolism and a contrasting dorsal raphé nucleus (DRN) hypermetabolism. Metabolism in these regions allows for the predictive classification of Nrxn1α genotype. Consistent with reduced mPrL glucose utilization, prefrontal cortex insulin receptor signaling is decreased in Nrxn1α +/− mice. Behaviorally, Nrxn1α +/− mice show enhanced learning of a novel discrimination, impaired reversal learning and an increased latency to make correct choices. In addition, male Nrxn1α +/− mice show hyperlocomotor activity. Correlative analysis suggests that mPrL hypometabolism contributes to the enhanced novel odor discrimination seen in Nrxn1α +/− mice, while DRN hypermetabolism contributes to their increased latency in making correct choices. The data show that Nrxn1 α heterozygosity impacts on prefrontal cortex and serotonin system function, which contribute to the cognitive alterations seen in these animals. The data suggest that Nrxn1α +/− mice provide a translational model for the cognitive and behavioral alterations seen in autism and other neurodevelopmental disorders associated with 2p16.3 deletion. Lay Summary: Deletion of the chromosomal region 2p16.3, involving reduced NEUREXIN1 gene expression, dramatically increases the risk of developing autism. Here, we show that reduced Neurexin1α expression, in mice, impacts on the prefrontal cortex and impairs cognitive flexibility. The data suggest that 2p16.3 deletion increases the risk of developing autism by impacting on the prefrontal cortex. Mice with the deletion are a useful model for testing new drugs to treat the cognitive flexibility problems experienced by people with autism.